ANALISIS PENGARUH DIGITAL BANKING TERHADAP PROFITABILITAS BANK - haryono, jesselyn julia; Widiyanti, Dwi Retno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The objective of this research is to identify the effects of digital banking on the profitability of banks by examining 71 Indonesian commercial banks that have published their Q1 financial statements during the 2019-2023 period. The profitability was measured using ROA (Return on Assets). The factors believed to affect the commercial banks’ profitability that are incorporated in this study are digital banking index, bank size, bank age and NPL. The digital banking index was acquired by measuring eleven facilities of digital banking. Using panel data regression, this study finds that digital banking index negatively and significantly influences the banks’ ROA, that bank size positively and significantly affects the banks’ROA, and that bank size and NPL do not have any impact on the banks’ ROA.